Shape-Memory-Recovery Characteristics of Microcellular Foamed Thermoplastic Polyurethane - Chang-Seok Yun (Polymers, 2020)
We investigated the shape-recovery characteristics of thermoplastic polyurethane (TPU) with a microcellular foaming process (MCP). Additionally, we investigated the correlation between changes in the microstructure and the shape-recovery characteristics of the polymers. TPU was selected as the base material, and the shape-recovery characteristics were confirmed using a universal testing machine, by manufacturing dog-bone-type injection-molded specimens. TPUs are reticular polymers with both soft and hard segments. In this study, we investigated the shape-memory mechanism of foamed polymers by maximizing the shape-memory properties of these polymers through a physical foaming process. Toward this end, TPU specimens were prepared by varying the gas pressure, foaming temperature, and type of foaming gas in the batch MCP. The effects of internal structural changes were investigated. These experimental variables affected the microstructure and shape-recovery characteristics of the foamed polymer. The generated cell density changed, which affected the shape-recovery characteristics. In general, a higher cell density corresponded to a higher shape-recovery ratio.